Leading Professional Learning : Tools to Connect and Empower Teachers. - Murray, Thomas C. (Corwin connected educators series., 2015)
Expert strategies for personalized, 21st Century professional learning! Empower teachers to take ownership of their own professional learning. Recognized EdTech leaders Murray and Zoul guide you step-by-step through the process. Confidently learn to build a values-driven school culture, personalized professional roadmaps, and a collaboration-minded staff. You'll find concrete examples, leadership profiles, and a wealth of resources to help administrators and teachers: Take ownership of their professional growth Design meaningful learning opportunities Collaborate and learn using technology, bl.